Exploring Awareness and Resistance to Nonattachment in Relation to Mental Health. A Qualitative Study in a UK-Based Yoga Community - Tremblay, Lindsay; Van Gordon, William (European Journal of Mental Health, 2023)
Introduction: Nonattachment is a flexible and balanced way of relating to experiences that involves accepting or allowing, instead of clinging to, expectations or outcomes. Advancing the understanding of how people relate to nonattachment is important because of the associated mental health benefits. Aims: To qualitatively explore awareness of, and resistance to, nonattachment in a UK-based yoga community. Methods: A reflexive thematic analysis was conducted based on transcripts of ten semi-structured interviews. Results: Findings indicated a general lack of consensus in understanding nonattachment, with explanatory themes of (i) resistance related to external forces conflicting with internal knowing, (ii) bracing for impact, and (iii) difficulty navigating how to embrace nonattachment. However, despite the participants’ apparent implicit negativity towards nonattachment, they acknowledged its benefits for accommodating change. Conclusions: These findings have important implications for the wider adoption and application of nonattachment in applied settings.